Overall Quality of Sporting Events and Emotions as Predictors of Future Intentions of Duathlon Participants - Magaz-González, Ana Mᵃ; Sahelices-Pinto, César; Mendaña-Cuervo, Cristina; García-Tascón, Marta (Frontiers in Psychology, 2020)
The present study is intended to analyse the effect of global quality, perceived value, general satisfaction and emotions on future behaviour patterns among participants in European Duathlon Championship. In this sense, a questionnaire was administered (n=210) composed of four sections: essential demographic and profiling variables, perceived quality, overall quality and emotions. Consequently, a relational model was designed to be examined by means of structural equation modelling (SEM) and fuzzy set qualitative comparative analysis (fsQCA). Results reveal that the global quality and the general satisfaction are key dimensions at the time of determining future behaviours of participants, but not so the perceived value. Moreover, up to three combinations of these dimensions together with emotions -pleasure and arousal- emerged as enough for depicting future intentions to a great extent. In this line, a remarkably sufficient combination consists of global quality, general satisfaction, pleasure and arousal. These findings will guide organisers to design strategies that provide exciting experiences, as well as quality and satisfaction to the participants of sports events.